Yield and economics of pigeonpea as influenced by foliar application of pulse magic - PATIL, J R; TEGGELLI, RAJU G; THAKUR, VIJAYSINGH (The Indian Journal of Agricultural Sciences, 2021)
The low yield of pigeonpea is due to flower drop and this is a major cause which contributes for much reduced potential yield of pigeonpea. If this major problem is reduced, then there will be attainment of maximum potential yield of the crop. This major problem can be minimized by foliar application of Pulse Magic (nutrients and plant growth regulators) during 50% flowering stage and 15 days after first spray. In addition to reduction in flower drop the increment in seed yield to the extent of 20% can be obtained due to foliar application of pulse magic as compared to control. Due to greater seed yield higher income could be generated-which is pre-requisite for sustainability.